The Impact of Globalization on Economies of Developed Countries - Pelegrinová, Lenka; Lačný, Martin (Journal of Economic Development, Environment and People, 2013)
The concept of globalization is interpreted by various authors in terms of its importance or content. This article presents results of an analysis of the influence of globalization trends on important macroeconomic indicators of selected countries. An examination of the level of globalization as a quantitative marker was enabled by the KOF Index of Globalization, which provides an indication of the economic, political and social globalization at global level. Research methods included time series analysis, trend analysis and nonparametric regression model (regression of panel data).